Phillips-Perron-type unit root tests in the nonlinear ESTAR framework - Christoph Rothe; Philipp Sibbertsen (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2005)
In this paper, we propose Phillips-Perron type, semiparametric testing procedures to distinguish a unit root process from a mean-reverting exponential smooth transition autoregressive one. The limiting nonstandard distributions are derived under very general conditions and simulation evidence shows that the tests perform better than the standard Phillips-Perron or Dickey-Fuller tests in the region of the null. – – In dieser Arbeit schlagen wir semiparametrische Tests vor, um Prozesse mit Einheitswurzeln von mean-reverting ESTARModellen zu unterscheiden. Die Tests sind vom Typ des Phillips-Perron Tests. Die Grenzverteilung der Teststatistiken wird unter sehr allgemeinen Annahmen hergeleitet. Eine Simulationsstudie zeigt, dass die Tests im Bereich der Nullhypothese bessere Eigenschaften haben als der Standard Phillips-Perron Test oder der Dickey-Fuller Test.
Keywords: C32; C12; 330; Exponential smooth transition autoregressive model; Unit roots; Monte Carlo simulations; Purchasing Power Parity